Análise da prevalência de mucosite oral em pacientes submetidos à radioterapia para câncer de cabeça e pescoço - França, Samuel Rocha (2024)
Radiotherapy is a widely used antineoplastic treatment modality, especially in the head and neck region. This method employs ionizing radiation, which destroys rapidly growing cells. Despite its effectiveness, this treatment presents adverse reactions in the oral cavity. The most common adverse reactions are radiation-induced mucositis, dysgeusia, xerostomia, opportunistic infections, radiation caries, osteoradionecrosis, and trismus. Oral mucositis is one of the most significant side effects in the oral cavity of patients undergoing antineoplastic treatments such as radiotherapy and chemotherapy. It is the most common cause of pain in the oral region. Therefore, knowledge about its prevalence and dose-dependence relationship will provide important data for a better understanding of the clinical course of these lesions. The aim of this study was to evaluate the prevalence of radiation-induced oral mucositis in patients undergoing radiotherapy in the head and neck region. A retrospective study was developed to investigate all medical records of patients who underwent radiotherapy in the head and neck region at Santa Casa de Misericórdia de Sobral from 2020 to 2023.Of the 129 patients included in the study sample, 87 (67.4%) were male and 42 (32.6%) were female. The predominant age range was 60 to 96 years (81 cases, 62.8%). The most prevalent neoplastic site was extrabucal, including the pharynx, hypopharynx, and facio-cervical sites, with 87 cases (67.4%). However, the site with the highest prevalence of mucositis was intrabucal, where out of the 47 cases analyzed, 26 patients showed some degree of mucositis, representing a prevalence rate of 61.9%. Cases of mucositis in extrabucal sites were 24 (27.6%) out of 63 (72.4%) patients with extrabucal neoplasms. The session interval with the highest prevalence of mucositis was between the 1st and 10th sessions, representing 15 (61.5%) affected cases. Among the patients who developed mucositis, the average dose per session was 200 cGy. The highest grade in the present study was grade 3 (9.3%), represented by a stage of mucositis in which the patient is fed a liquid diet. Thus, the importance of dental follow-up by the dentist is emphasized to perform preventive and curative oral health actions during the pre-radiotherapy stage, during treatment, and post-treatment, ensuring better quality of life for the patient and contributing to the effectiveness of the antineoplastic treatment.